How Power Changes Hands
XI, 254 p.
Keywords: How can we strengthen the capacity of governments and parties to manage arrivals and departures at the top? Democracy requires reliable processes for the transfer of power from one generation of leaders to the next. This book introduces new analytical frameworks and presents the latest empirical evidence from comparative political research.